(3GdEOGQI GdJQHhjI GdMOjKIs - (3TQHd, ehQjSs ((3HjQhJs (3OGQ GdacQ GdYQHjs, 2007)
(3jYJHQ gPG GdcJGH HeKGHI fGaPI LOjOI JWd efgG Ydi YGde GdEOGQI GdMOjKI YHQ GdMGShH hGdEfJQfJ, ajTcd HPdc EWdGdI LOjOI ddEOGQI GdJQHhjI(B.s
(3GdfhY (B: (3cJGHs
Keywords: Administration Scolaire; Education moderne; Educational administration; Modern education; (3GdGOGQI GdJQHhjIs; (3GdJQHjI GdMOjKIs